통계기법을 이용한 도시 하수처리시설의 합리적 소요면적 산정에 관한 연구 - 구동현(Donghyun Koo); 박노석(No-Suk Park); 오정익(Jeong Ik Oh); 윤석민(Sukmin Yoon) (Daehan hwan'gyeong gonghag hoeji, 2020)
목적:본 연구에서는 국내 하･폐수처리설의 소요면적, 하부 시설물별 점용비율 및 처리 공법 등을 대상으로 다양한 자료 분석을 통해 합리적인 처리용량-소요면적 산정 방법론을 제시하고, 이러한 방법론을 적용하는 경우 실제 하･폐수처리설의 예상 소요면적 절감효과를 정량적으로 평가하고자 하였다. 방법:국내 지자체에서 건설 및 운영 중인 하･폐수처리시설 중 500 m3/day 이상 654개소 자료 및 한국토지주택공사(LH)에서 건설한 33개소 자료를 취득하여 총 687개소의 자료를 통계분석 하였다. 그리고 대상 표본 집단 중 LH에서 건설한 33개소 하･폐수처리시설에 대해서는 기능별로 구성 면적을 구분하고 각 시설별 점용비율에 대한 분석을 수행하였다. 결과 및 토의:수집된 표본 집단들을 대상으로 처리용량-소요면적 관계식을 개발하고 기존의 연구들과 비교한 결과 관계식의 분포 형태는 분석 표본 집단 차이에 따라 2개의 군집으로 분리되었다. 그리고 전국 단위의 표본 집단을 활용한 관계식들의 추정 소요면적이 LH 단위의 표본 집단을 활용한 관계식들에 비해 상대적으로 높은 소요면적을 추정하는 것으로 분석되었다. 본 연구에서는 LH 단위의 표본 집단 분석결과를 활용해 하･폐수처리장의 녹지부지 점용비율 및 처리공법 집약화에 따른 예상 소요 면적 감소 효과를 포함한 처리용량-소요면적관계식을 다음과 같이 제안하였다. , 여기서 는 하･폐수처리장 내 녹지부지(녹지를 제외한 시설 면적의 10~150%)를 고려한 환산계수()로 정의되며, 는 처리공법에 따른 환산계수로서 MBR/SBR 공법 적용 시 0.75, A2O공법 및 관련 변법 적용 시에는 1.0을 적용하게 된다. 결론:최근 계획 및 설계단계의 하수처리 시설들은 분산화 및 소규모화 추세에 있으며, 도입되는 하수 고도처리 공법이 MBR/SBR과 같이 상대적으로 작은 소요면적을 필요로 하는 공법의 도입이 가속화되고 있음에 본 연구에서는 계획 및 설계 단계에서부터 적용 가능한 개선된 소요면적 관계식을 제안하였다. 그리고 본 연구에서 제안한 처리용량-소요면적 추정 방법론을 적용하여 실제 예상 소요 면적 절감효과를 정량적으로 평가한 결과 최대 약 50~60% 정도의 규모에서 소요면적을 줄일 수 있을 것으로 기대된다. Objectives:In this study, a adjusted sewage & wastewater treatment capacity-required area estimation methodology was proposed through various data analysis for the required area of domestic sewage & wastewater treatment, the occupancy ratio of each sub-facility, and the treatment processing method. In addition, the reduction rate of the required area according to the application of the adjustment methodology presented in this study was evaluated quantitatively by comparing the actual area with the expected area. Methods:Statistical analysis was performed by collecting 654 data of more than 500 m3/day of treatment capacity in domestic sewage & wastewater treatment facilities. The 33 sewage & wastewater treatment facilities constructed by the LH sample groups were divided into functional areas and analyzed for occupancy rates by each facility. Results and Discussion:A capacity-required area regression model was developed for the collected each samples. As a result, the distributions of the regression model were divided into two clusters according to the analysis sample differences. It was analyzed that the estimated required area using the local government sample group was estimated to be relatively higher than the LH sample group. In this study, a adjusted capacity-required area model based on regression model derived from LH sample was proposed by considering green site ratio and treatment processing methods in sewage & wastewater treatment plant. The results are as follows: (: conversion factor for green site ratio, : conversion factor for treatment processing method). Conclusions:Recently, the wastewater treatment facilities have been in decentralization and small scale, and the introduction of the advanced treatment method that requires a relatively small area such as MBR or SBR has been accelerating. Consequently, it could be expected that the methodology proposed in this study will save about 50~60% of the required area for wastewater treatment facilities. KCI Citation Count: 0